Laser Doppler Flowmetry In Orthodontıcs - Cenk Doruk; Hasan Babacan (Galenos Yayinevi, 2003)
Laser Doppler flowmetry (LDF) has been first used in medical science in 1972 and also commonly being used in dentistry in the recent years. The history, using principles, advantages and disadvantages, structure and the use of LDF in the dentistry and orthodontics has been presented in this article.